Cognitive performance in UK sample of presymptomatic people carrying the gene for Huntington's disease. Issue 5 (May 1995) - Blackmore, L; Simpson, S A; Crawford, J R
Abstract : This paper presents an investigation of cognitive ability in 30 subjects at risk for Huntington's disease. Those shown to be at high or low risk for this disease are compared on a wide range of neuropsychological measures. Results indicate only one significant difference between the two groups; those who carry the gene show a higher level of performance on the Corsi Supraspan task. It is suggested, however, that minimal deficits are apparent in the at risk gene carrying group but that current measures of assessment are not sensitive enough to identify them.